Expression and physicochemical characterization of an N-terminal polyhistidine-tagged phosphotriesterase from the soil bacterium Brevundimonas diminuta. (October 2020) - Chi, Meng-Chun; Liao, Ting-Yu; Lin, Min-Guan; Lin, Long-Liu; Wang, Tzu-Fan
Abstract: In this study, a truncated organophosphate-degrading ( opd ) gene encoding a Brevundimonas diminuta phosphotriesterase ( Bd PTE) without its leader peptide was artificially synthesized and cloned into the expression vector pQE-30 to yield pQE- Bd PTE. The His6 -tagged 37.8-kDa enzyme was purified from the cell-free extract of isopropyl thio-β-d -galactoside (IPTG)-induced E. coli M15 (pRep4) cells harboring pQE- Bd PTE to near homogeneity by metal chelate affinity chromatography. The assay conditions for His6 -tagged Bd PTE activity were optimized at 60 °C, pH 8.0, and 1.0 mM Co 2+ ion. Kinetic analysis of His6 -tagged Bd PTE-catalyzed hydrolysis of diethyl p -nitrophenyl phosphate (paraoxon-ethyl) showed that its K m and k cat values were 21.9 ± 1.4 μM and 311.6 ± 12.3 s −1, respectively. Also, the recombinant enzyme had the ability to efficiently degrade the two most commonly used OP pesticides, ethion and fenthion, in Taiwan. His6 -tagged Bd PTE with 1 mM Co 2+ was very stable during the storage period of 35 days at 4 °C. Urea- and guanidine hydrochloride (GdnHCl)-induced denaturation studies showed that the purified enzyme had [denaturant]0.5, N – U values of 6.7 and 3.4 M, respectively. Notably, His6 -tagged Bd PTE did exhibit some degree of tolerance to a variety of water-miscible organic co-solvents. Dimethyl sulfoxide (DMSO), acetone, dimethylformamide (DMF), and ethanol were obviously harmful to the hydrolytic activity of the enzyme at concentrations above 50% (v/v), while acetonitrile was the highest tolerated co-solvent. The organic solvent-tolerant feature verifies His6 -tagged Bd PTE highly suitable as a remediation agent for the biodegradation of non-polar OP pesticides. Highlights: A recombinant phosphotriesterase of B. diminuta (His6 -tagged Bd PTE) is successfully expressed in E. coli. His6 -tagged Bd PTE has the ability to efficiently hydrolyze ethion and fenthion. The recombinant enzyme is very stable in the presence of 1 mM Co 2+ . The [denaturant]0.5, N –U values of urea and guanidine hydrochloride for the enzyme are 6.7 and 3.4 M, respectively. His6 -tagged Bd PTE exhibits a high degree of tolerance to acetonitrile.